(untitled) (Marketing Journal, 2025)
This article examines and studies the characteristics and classification of mandatory insurance reserves. Also, proposals and recommendations have been developed for reflecting operations related to mandatory insurance reserves in accounting accounts and accounting entries. In particular, conclusions were formulated with the development of an authorʼs approach to the composition of mandatory insurance reserves and the current state of operations related to them, as well as their improvement.